2006
DOI: 10.1080/10790268.2006.11753902
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Biochemical Profiles of Mid-Cervically Located Adenosine A1 Receptors After Repeated Theophylline Administration in Adult Rats

Abstract: Background/Objective: Adenosine A 1 receptors localized in the phrenic motoneurons (PMNs), where the axons of the descending bulbospinal respiratory make synaptic contacts, may be involved in theophyllineinduced respiratory-related activity in rats. The objective of this study was to characterize the biochemical profiles of adenosine A 1 receptors in 2 groups of rats: (a) naïve and (b) theophylline-treated (3-day oral administration).Methods: Biochemical binding characteristics of adenosine A 1 receptors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Notably, theophylline (Shahzadi et al, 2020;Shahzadi et al, 2022a), a naturally occurring methylxanthine, has found frequent therapeutic use in treating conditions such as asthma, respiratory deficits in premature infants, and chronic pulmonary obstructive disease (COPD). It also functions as a phosphodiesterase inhibitor (Ito et al, 2002;Saharan and Nantwi, 2006). Acefylline (Shahzadi et al, 2022b), a derivative of theophylline with pharmacological activity, serves various purposes, including bronchodilation, heart stimulation, diuresis, smooth muscle relaxation, antimicrobial and antituberculosis properties, and antiinflammatory effects (Foppoli et al, 2007;Mangasuli et al, 2018;Gopinatha et al, 2020;Shahzadi et al, 2020;Shahzadi et al, 2022a;Montaño et al, 2022), as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, theophylline (Shahzadi et al, 2020;Shahzadi et al, 2022a), a naturally occurring methylxanthine, has found frequent therapeutic use in treating conditions such as asthma, respiratory deficits in premature infants, and chronic pulmonary obstructive disease (COPD). It also functions as a phosphodiesterase inhibitor (Ito et al, 2002;Saharan and Nantwi, 2006). Acefylline (Shahzadi et al, 2022b), a derivative of theophylline with pharmacological activity, serves various purposes, including bronchodilation, heart stimulation, diuresis, smooth muscle relaxation, antimicrobial and antituberculosis properties, and antiinflammatory effects (Foppoli et al, 2007;Mangasuli et al, 2018;Gopinatha et al, 2020;Shahzadi et al, 2020;Shahzadi et al, 2022a;Montaño et al, 2022), as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%